Respuesta :

Answer:

144

Step-by-step explanation:

Perfect square formula: a^2 - 2ab + b^2 (because that equals (a-b)^2)

x^2-2*12x+c

a = 1

b = 12

12^2 = 144

Answer:

The value of [tex]c =144[/tex] makes [tex]x^{2}-24x+c[/tex] perfect square.

Step-by-step explanation:

We have to make [tex]x^{2}-24x+c[/tex]

Since, Perfect square formula: [tex]a^{2} - 2ab + b^{2}=(a-b)^{2}[/tex]

Re-write [tex]x^{2}-24x+c[/tex] as,

[tex]x^{2}-2\times 12x+c[/tex]

Compare above with [tex]a^{2} - 2ab + b^{2}[/tex]

Where a = x  and b= 12

so, [tex]b=12[/tex]

[tex]c =12^{2}=144[/tex]

Hence, [tex](a-b)^{2}=(x-12)^{2}[/tex]

Therefore, the value of [tex]c =144[/tex] makes [tex]x^{2}-24x+c[/tex] perfect square.

ACCESS MORE